Effects of Parathyroid Hormone on Immune Function - Abdallah Sassine Geara; Mario R. Castellanos; Claude Bassil; Georgia Schuller-Levis; Eunkue Park; Marianne Smith; Michael Goldman; Suzanne Elsayegh (Clinical and Developmental Immunology)
Parathyroid hormone (PTH) function as immunologic mediator has become interesting with the recent usage of PTH analogue (teriparatide) in the management of osteoporosis. Since the early 1980s, PTH receptors were found on most immunologic cells (neutrophils, B and T cells). The in vitro evaluations for a possible role of PTH as immunomodulator have shown inconsistent results mainly due to methodological heterogeneity of these studies: it used different PTH formulations (rat, bovine, and human), at different dosages and different incubating periods. In some of these studies, the lymphocytes were collected from uremic patients or animals, which renders the interpretation of the results problematic due to the effect of uremic toxins. Parathyroidectomy has been found to reverse the immunologic defect in patients with high PTH levels. Nonetheless, the clinical significance of these findings is unclear. Further studies are needed to define if PTH does have immunomodulatory effects.